2016
DOI: 10.1523/jneurosci.0512-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase 1 Is Indispensable for Development of the Hippocampal Dentate Gyrus

Abstract: Development of the hippocampal dentate gyrus (DG) in the mammalian brain is achieved through multiple processes during late embryonic and postnatal stages, with each developmental step being strictly governed by extracellular cues and intracellular mechanisms. Here, we show that the maintenance DNA methyltransferase 1 (Dnmt1) is critical for development of the DG in the mouse. Deletion of Dnmt1 in neural stem cells (NSCs) at the beginning of DG development led to a smaller size of the granule cell layer in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 57 publications
3
22
2
Order By: Relevance
“…We have previously reported that the enzyme DMNT1 is highly expressed in NSCs in both embryonic and adult brains. 19,36 However, in contrast to the results obtained for prenatal deletion, loss of Dnmt1 in NSCs during the adult stage impairs neither proliferation nor neuronal differentiation of NSCs. 16 Furthermore, upregulation of GFAP expression and activation of microglia in the adult brain were not observed in mice lacking Dnmt1 in NSCs (data not shown).…”
contrasting
confidence: 64%
See 4 more Smart Citations
“…We have previously reported that the enzyme DMNT1 is highly expressed in NSCs in both embryonic and adult brains. 19,36 However, in contrast to the results obtained for prenatal deletion, loss of Dnmt1 in NSCs during the adult stage impairs neither proliferation nor neuronal differentiation of NSCs. 16 Furthermore, upregulation of GFAP expression and activation of microglia in the adult brain were not observed in mice lacking Dnmt1 in NSCs (data not shown).…”
contrasting
confidence: 64%
“…Mice that had undergone prenatal deletion of Dnmt1 were allowed to mature until adulthood and displayed no obvious defects in body size, brain structure, or brain weight. 19 Previously, we reported that prenatal deletion of Dnmt1 impairs adult neurogenesis in the DG. 19 However, the influence of such deletion on adult neurogenesis in the SVZ remains to be examined.…”
mentioning
confidence: 98%
See 3 more Smart Citations